Land suitability for paddy and maize in a watershed using remote sensing and Geographic Information System(GIS) - SYED, MAHEENA; KHAN, JUNAID N.; KUMAR, ROHITASHW; DAR, ISHFAQ AHMED (Journal of Soil and Water Conservation, 2020)
Land evaluation using a scientific procedure is essential to assess the potential and optimum utilization of the available land resources and sustainable agricultural production. The present study was conducted in Sind watershed (9423.20 ha) of district Ganderbal of Jammu and Kashmir to assess the suitability for land of paddy and maize. Land use/Land cover maps were also prepared to analyze the existing crops using ArcMap 10.2 software. The land suitability evaluation was carried out on the basis of parameters of soil depth, texture, slope, drainage and erosion.Each of these parameters were separately analyzed for their suitability for supporting paddy and maize crops based on the FAO crop requirements specified for them. Suitability maps for crop of paddy and maize were generated in ArcMap 10.2. From the suitability maps it was observed that out of total area of 9423.2 ha, about 88% is moderately suitable and 12% area (1153.6 ha) is marginally suitable for paddy cultivation. In case of maize, about 4.3% area (405.5 ha) is highly suitable, only 0.3% area (30ha) is moderately suitable, 89.6% area (8440.25ha) is marginally suitable and 5.8% area (547.45 ha) is not suitable for maize cultivation.The study revealed that satellite remote sensing(RS) and GIS technique has been found to be most essential tool for the land suitability